Evolution and concretization of the bona fide purchaser in civil law tradition - Sabirov, K.K. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The article aims to analyze evolution and concretization of the bona fide purchaser in the Civil law tradition. The research begins by overviewing the status of the bona fide purchaser in Roman law and its legal basis. The article then delves into the history of the issue to show how classical Roman law was modernized with the customs of Germanic tribes which led to the formation of Civil law. Finally, the article describes the further evolution of the concept of the bona fide purchaser in the legislation of countries in the Civil law tradition. The research is based on the works of German, English, French, US, and Russian lawyers who have dealt with issues of the bona fide purchaser. The study uses the method of historical comparison and system analysis to provide a deeper understanding of the concept of the bona fide purchaser in Civil law tradition. The results of the research can significantly deepen the theory of Civil law and are recommended for scholars and practitioners interested in the history and theory of law. The research based upon the method of historical comparison and system analysis. The results of the research allow distinguishing two types of bona fides that is used in the Civil law tradition: in objective and in subjective sense.